Gene Expression in B-1 Cells from Lupus-Prone Mice. (October 2014) - Novaes e Brito, Ronni Rômulo; Xander, Patricia; Pérez, Elizabeth C.; Maricato, Juliana T.; Laurindo, Maria FL.; De Lorenzo, Beatriz H P.; Pellegrino, Renata; Bernardo, Viviane; Lopes, José Daniel; Mariano, Mario
<x xml:space="preserve">Abstract</x> New Zealand Black X New Zealand White F1 [(NZB/NZW)F1] mice develop an autoimmune condition with similarities to human systemic lupus erythematosus (SLE). In this study, we demonstrate that B-1 cells, which have previously been reported to be involved in several autoimmune diseases, have altered gene expression in these mice. RNA was extracted from purified B-1 cells of disease-free C57BL/6 mice and lupus-prone (NZB/NZW)F1 mice. Gene expression was analysed using DNA microarray techniques and validated by real time reverse transcriptase polymerase chain reaction (RT-PCR). In (NZB/NZW)F1 mice, some genes had altered expression patterns compared to disease-free controls. Specifically, the upregulation of Ifitm1, Pvrl2 and Ifi202b and downregulation of Trp53bp1 mRNA were observed in (NZB/NZW)F1 mice. These genes are known to be associated with autoimmune diseases. This pattern of gene expression in B-1 cells could understanding of the pathogenesis of SLE. Thus, it is reasonable to hypothesise that the altered gene expression observed in B-1 cells in our experimental model is important for SLE prognosis and therapy, and these implications are discussed herein.